2002
DOI: 10.1002/mus.10086
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level exposures to organophosphorus esters and peripheral nerve function

Abstract: This review evaluates the epidemiological and clinical evidence linking low-level and prolonged exposures to organophosphorus esters, used as insecticides or nerve agents, to peripheral nerve dysfunction. The clinical effects of large doses of these chemicals-including the cholinergic syndrome, the intermediate syndrome, and the delayed polyneuropathy-are all well established and are summarized. Based on these clinical observations and experimental studies, dose-effect relationships indicate that peripheral ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 87 publications
(84 reference statements)
0
36
0
Order By: Relevance
“…Another possibility is that our farmers were exposed to low levels of pesticides and that these levels were not high enough to produce other symptoms. Indeed, several studies on low-level exposure to AChE have reported mild, inconsistent, and unexplained changes of the peripheral nerve system [7,33,34]. Acute poisoning is well defined in terms of threshold, but low-level effects shade into range of non-specific symptoms [7].…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that our farmers were exposed to low levels of pesticides and that these levels were not high enough to produce other symptoms. Indeed, several studies on low-level exposure to AChE have reported mild, inconsistent, and unexplained changes of the peripheral nerve system [7,33,34]. Acute poisoning is well defined in terms of threshold, but low-level effects shade into range of non-specific symptoms [7].…”
Section: Discussionmentioning
confidence: 99%
“…Pesticide pollution has been recognized as an important global issue with scientists and environmental agencies tackling the problem with the development of more biocompatible pesticides which aim to minimise the side effects on the non-target species. However, even low levels of pesticides in drinking water may result in toxicity, with increased risk due to bio-accumulation and potential long term chronic effects [3,4]. In many cases, the environmental fate of pesticides is poorly understood, which is further complicated with the introduction of new ingredients in pesticide formulations [5].…”
Section: Introductionmentioning
confidence: 99%
“…There are also delayed effects for a subset of organophosphates. In humans, delayed chronic neurotoxic syndromes from exposure to individual organophosphates or combinations of agents have been reported for Gulf War veterans and chronically exposed individuals [3][4][5][6][7][8][9] . The most common and best understood delayed syndrome is organophosphate-induced delayed neuropathy (OPIDN).…”
Section: Introductionmentioning
confidence: 99%